A water-stable open-framework zirconium(iv) phosphate and its water-assisted high proton conductivity. Issue 35 (10th August 2021) - Yu, Jing-Wei; Yu, Hai-Jiao; Yao, Zhi-Yuan; Li, Zi-Han; Ren, Qiu; Luo, Hong-Bin; Zou, Yang; Wang, Lifeng; Ren, Xiao-Ming
Abstract : A water stable open-framework zirconium(iv) phosphate (ZrP ) has a low anhydrous proton conductivity of 7.73 × 10 −7 S cm −1 at 220 °C, and a water assisted high proton conductivity of 4.41 × 10 −2 S cm −1 at 60 °C and 98% RH. Abstract : A water stable proton-conducting material (NH4 )5 [Zr3 (OH)3 F6 (PO4 )2 (HPO4 )] (ZrP ) was hydrothermally synthesized. The three-dimensional (3D) framework of ZrP is composed of ZrF2 O4 octahedra and H x PO4 phosphate units forming 18-ring channels through sharing oxygen atoms. Ammonium cations charge balance the anionic framework. Alternating current (AC) impedance measurements on ZrP powder samples show that at 25–60 °C and 98% relative humidity (RH), the proton conductivity is around 10 −2 S cm −1, and the activation energy ( E a ) is 0.33 eV.